Demographic Characteristics and Cardiometabolic Risk Profiles of Ischemic Stroke Patients - Luh Nyoman Ananda Mahayati (Newinera Publisher, 2025)
Ischemic stroke remains a leading cause of morbidity and mortality globally and in Indonesia, with multifactorial risk factors involving vascular, metabolic, and lipid disorders. Understanding patient characteristics at the regional healthcare level is essential to support targeted clinical interventions. Bangli Regional General Hospital, as a referral hospital in Bali, has not yet systematically published data on ischemic stroke patient profiles, making this study important for local clinical planning. This retrospective descriptive observational study analyzed medical records of 160 ischemic stroke patients treated at Bangli Regional General Hospital throughout 2024. Variables included age, gender, hypertension, type 2 diabetes mellitus, history of heart disease, onset of arrival to the emergency department (<4.5 hours), and laboratory parameters comprising total cholesterol, LDL, HDL, triglycerides, and uric acid levels. Data were analyzed descriptively using frequencies, percentages, means, and standard deviations. Most patients were male (64.4%), with the largest proportion aged 60–75 years (38.75%), followed by middle-aged patients (32.5%). Hypertension was present in 67.5% of patients, type 2 diabetes mellitus in 15.6%, and a history of heart disease in 34.4%. Only 18.1% of patients arrived at the emergency department within 4.5 hours of symptom onset. Mean lipid values were 178.62 mg/dL for total cholesterol, 116.69 mg/dL for LDL, 45.31 mg/dL for HDL, and 123.35 mg/dL for triglycerides. Hyperuricemia was identified in 28.16% of men and 24.56% of women. Overall, ischemic stroke patients at Bangli Regional Hospital were predominantly elderly men with a high prevalence of hypertension and cardiometabolic abnormalities, reflecting national epidemiological patterns.